PENDETEKSIAN FINANCIAL STATEMENT FRAUD MENGGUNAKAN FRAUD HEXAGON PADA PERUSAHAAN YANG TERINDEKS IDXBUMN20 - Maulida, Maulida; Rahmazaniati, Linda; Vonna, Sari Maulida; Mahdani, Said; Fatmayanti, Fatmayanti (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This research has a problem with financial statement fraud with the smallest percentage of cases but has the greatest impact on state losses among other frauds. This study aims to detect financial statement fraud using fraud hexagon in IDXBUMN20 indexed companies. There are six dimensions in the fraud hexagon consisting of stimulus, ability (Capability), conspiracy (Collusion), opportunity (Opportunity), rationalisation, and (arrogance). This study measures financial statement fraud using the Beneish M-Score. The population of this study were 20 BUMN companies indexed on IDXBUMN20. To select the sample, purposive sampling method was used for 15 state-owned companies for 3 years of observation with 45 observations. Logistic regression model as an analysis technique. Data processing with SPSS 26 which obtained results showing that financial stability proxy stimulus, auditor turnover proxy opportunity and ineffective supervision proxy rationalization affect financial statement fraud. While the change of directors proxy capability, the number of independent commissioners who hold concurrent positions proxy collusion, and the number of CEO photos in the annual report proxy arrogance have no effect on financial statement fraud.